Roads to Nowhere? Cycling, Happiness and Emotional Authenticity in Contemporary German Fiction - Jon Hughes (Studies in 20th & 21st Century Literature, 2020)
This article compares a selection of recent German literary representations of cycling in the context of contemporary discourses of slow travel, with a particular focus on themes of happiness and emotional authenticity. It seeks to expand the framework of discussions of slow travel with a comparative focus on four novels: Der Mann auf dem Hochrad (‘The Man on the Penny Farthing’, 1984) by Uwe Timm, Im Sommer wieder Fahrrad (‘I’ll Cycle Again in the Summer’, 2016) by Lea Streisand, Im Feld (‘In the Field’, 2018) by Joachim Zelter and Neujahr (‘New Year’, 2018) by Juli Zeh. The article surveys the cultural history of cycling, and pays attention to the status of cycling in German society and culture. Drawing on the work of John Day, Valeria Luiselli, Erling Kagge and Mihaly Csikszentmihalyi, it presents a reading of the texts’ treatment of cycling as performance within a broader reflection upon slow travel as a non-functional, affective and authentic practice is experienced as a contrast to everyday life.
Keywords: cylcing; cycling in Germany; cycling in literature; German literature; travel writing; slow travel; Uwe Timm; Lea Streisand; Joachim Zelter; Juli Zeh; history of sport; history of leisure; tourism in literature; emotions in literature; happiness in literature; psychology and literature